Caracterização da cobertura superficial em cabeceira de drenagem sobre substrato vulcânico - Campo Erê (SC) - Bragas, Luciléia Aparecida Silveira dos Santos (2010)
This paper presents characteristics of the surface coverage found in bedside drainage developed on volcanic substrate, in the Upper Rio Sergento Course (Campo Erê - SC). The descriptions of the materials were made by sampling along five transects, and the opening of three trenches. The physical attributes of materials associated with the analysis of particle size and volume compared with the topography point to allow pedogenesis as the main factor in the evolution of bedside drainage, mainly over the nose and side slope. In the hollow were identified two deposits of colluvium. The association of physical and chemical properties of surface coverage to classify the soil at the head of this drainage as oxic soils, from red to dark reddish nose to bruno on side slope. The clay minerals as revealed by X-ray diffraction in surface coverage over the nose and side slope of bedside drainage geochemical study indicate hydrolysis intense situation in the area. The largest number of peaks of kaolinite shows an environmental geochemist with a predominance of monossialitization process. Less intense, the process also occurs alitização, being filed by gibbsite. Considering the role of geochemical processes, as well as the occurrence of kaolinite dominant on clay less frequent as vermiculite and gibbsite, the indices obtained and disclosed by routine chemistry, the surface coverage of the nose and side slope, at the bedsiders of drainage studied fits as ferruginous desaturated.